2018
DOI: 10.1002/jcb.27897
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Downregulation of long noncoding RNA SNHG1 inhibits cell proliferation, metastasis, and invasion by suppressing the Notch‐1 signaling pathway in pancreatic cancer

Abstract: Background Pancreatic cancer (PC) has become the fourth most lethal among human cancers. Long noncoding RNAs (lncRNAs) have been reported to play a role in the progression of a variety of cancers. However, the role of lncRNA SNHG1 in PC is not clear. Methods Real‐time Quantitative PCR Detection System (qPCR) was used to detect the expression of SNHG1 in PC cells. Then, the SNHG1 knockdown cell was constructed with si‐SNHG1. AsPC‐1 and PANC1 cells were used to analyze the ability of cell proliferation, invasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…Moreover, Gao et al ( 20 ) revealed that lncRNA zinc finger E-box binding homeobox 2 AS1 increased the proliferation, migration and invasion, but reduced the apoptosis of bladder cancer cells as competing endogenous RNA sponges microRNA (miR)-200b to elevate the expression of fascin-1. Previous studies have also reported that SNHG1 serves important roles in the progression of cancer types, including NSCLC ( 21 ), glioma ( 9 ), pancreatic cancer ( 22 ), cholangiocarcinoma ( 23 ) and osteosarcoma ( 24 ).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, Gao et al ( 20 ) revealed that lncRNA zinc finger E-box binding homeobox 2 AS1 increased the proliferation, migration and invasion, but reduced the apoptosis of bladder cancer cells as competing endogenous RNA sponges microRNA (miR)-200b to elevate the expression of fascin-1. Previous studies have also reported that SNHG1 serves important roles in the progression of cancer types, including NSCLC ( 21 ), glioma ( 9 ), pancreatic cancer ( 22 ), cholangiocarcinoma ( 23 ) and osteosarcoma ( 24 ).…”
Section: Discussionmentioning
confidence: 98%
“…Many studies have shown that the occurrence of invasion and metastasis in pancreatic cancer patients indicates a poor prognosis [15][16][17][18][19] . In our study, we used a series of experiments to obtain insight into the biological effects of LINC00673 in pancreatic cancer proliferation and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…SNHG1 was reported to be remarkably upregulated in several types of human malignancies such as osteosarcoma and laryngeal squamous cell carcinoma (LSCC) 84,86,87 . SNHG1 knockdown obviously impeded tumour cell proliferation, migration and invasion, while induced apoptosis via participating in pleiotropic cancer‐related signalling pathways, such as Notch, 88 Wnt/β‐catenin 87 and Hippo pathway 84 . Specifically, SNHG1 could serve as ceRNA to sponge to miR‐375 and thus promote YAP expression to regulate Hippo pathway in LSCC.…”
Section: Regulatory Network Of Lncrnas and Hippo Signalling Pathway Imentioning
confidence: 99%